Chlorination of N-phenylbenzenesulfonamides with NCP in aqueous acetic acid. Using the para/meta ratio of substituent effects for mechanism elucidation - Reis, JCR (2015)
Rate constants were measured for the oxidative chlorination reaction of N-phenylbenzenesulfonamide 2 and twelve ortho-, nine meta- and twelve para-substituted derivatives in the aniline moiety, using 1-chloro-3-methyl-2,6-diphenylpiperidin-4-one ( 1) as chlorinating agent. The kinetics was run in 50% (v/v) aqueous acetic acid acidified with perchloric acid under pseudo-first-order conditions with respect to 1 at five different temperatures between 298 and 318 K. The dependence of rate constants on temperature was analysed in terms of the isokinetic relationship (IKR). The resulting isokinetic temperature was estimated to be 513 K. Using the Linert's theory of the IKR, the experimental isokinetic temperature was interpreted as evidence for the preferential involvement of water molecules in the formation of activated complexes. The dependence of the rate constants on the substituents was analysed using the tetralinear extension of the Yukawa-Tsuno equation for the effects of meta and para substituents. A positively charged transition state was suggested by an experimental value r(+) = 0.39 for the resonance demand, which was found to be insensitive to temperature variation. The parameter. for the para/meta ratio of substituent effects was estimated to be 0.952. The electrostatic modelling of. values was re-examined in the light of the recent calculations of the energies of interaction between charged and/or dipolar groups by Exner and Bohm. Based on energy ratios, the electrostatic method was shown to remain valid for the purpose of modelling. values. The experimental. value for the reaction indicates the formation of an activated complex possessing an electric charge in the vicinity of the nitrogen atom of the substrate. The electrophilic attack on the substrate nitrogen atom by the protonated chlorinating reagent has been proposed as the rate-determining step, with the last step being the fast rearrangement of the intermediate N-chloro-N-phenylbenzenesulfonamidium cation into the products.